Fruit Fly (Diptera: Tephritidae) Host Status and Relative Infestation of Selected Mango Cultivars in Three Agro Ecological Zones in Uganda. Issue 1 (2nd January 2016) - Isabirye, B. E.; Akol, A. M.; Muyinza, H.; Masembe, C.; Rwomushana, I.; Nankinga, C. K.
ABSTRACT: Despite their economic importance, there is paucity of knowledge on fruit fly host status in Uganda. Therefore, this study set out to profile the host range of the main fruit fly pests and determine the susceptibility of selected fruits and mango cultivars across three main mango agro ecological zones, which included: Western Medium High Altitude Farmlands (WMHF), Lake Victoria Crescent (LVC), and the Northern Moist Farmlands (NMF) in Uganda. A wide range of fruits was sampled across the three zones. These were incubated at the National Agricultural Research Laboratories following standard protocols. Emerging fruit fly species were identified using standard keys and counted. Among the sampled fruits, 633 (35.0%) individual fruits from 15 plant families were positive for fruit fly infestation. Bactrocera invadens dominated (76.3%) of the positive samples, while infestation by native species, such as Ceratitis capitata and Ceratitis cosyra, was negligible. Annonaceae, Solanaceae, Rutaceae, and Anacardiaceae plant families recorded significantly more host species, while the number of pest fruit flies (species richness) per plant species followed a similar trend: Solanaceae > Rutaceae > Anacardiaceae. There was significant (P < 0.0001) variability in infestation among mango fruit cultivars, both within and across zones. When all zones were pooled together, Tommy Atkins and Kent, and Keitt, Kate, and Biire were the least and most infested, respectively. In conclusion, fruit flies have a diverse range of commercial and non-commercial hosts in Uganda. Strategies for fruit fly pest eradication in the country should ensure elimination or management of alternative fruit hosts and integration of tolerant mango cultivars in fruit development programs.